Study of Port-site and Intraperitoneal Infiltration of Local Anesthetics in Reduction of Postoperative Pain after Laparoscopic Cholecystectomy - Abidi, Aliza; Neelum Agha, Shahzadi; Yousaf, Aasia; Shah, Farah; Shaikh, Maria; Qaiser, Saba (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To evaluate the efficacy of bupivacaine administered by intraperitoneal versus port-site infiltration for postoperative pain management following laparoscopic cholecystectomy (LC). Methods: A total of 80 patients who underwent elective LC between March 2022 and March 2023 were included. Patients were randomly assigned to one of the two study groups. After removal of the gall bladder from the patient in group A, a solution of bupivacaine with a concentration of 0.5% was injected into the right subdiaphragmatic area, along with 20 milliliters of bupivacaine solution was also injected into the port sites. While in Group C only standard analgesic management was performed and no wound infiltration was performed. Post-operative pain was the primary study outcomes. Results: Mean age was 38.49±14.78 years in group A and 40.18±13.81 years in group B with p-value 0.53. There was majority 31 (77.5%) females in group A and 32 (80%) females in group B, p-value 0.78. Mean NRS score after 4 hours of LC was 4.51±1.42 in group A and 5.11±1.10 in group C (p-value 0.03). Mean NRS score after 6 hours was 3.7±0.80 in group A versus 4.25±1.05 in group C (p-value 0.03). Mean NRS score after 12 hours was 2.56±0.75 in group A versus 3.23±0.90 in group C (p- value <0.001). However, at 24 hours of surgery the mean NRS score became statistically insignificant with p-value 0.37. Mean requirement of tramadol as rescue analgesia was also significantly lower in study group. Practical Implication: The study found that while demographic variables were similar across groups, there were significant differences in pain management outcomes. Group A showed lower NRS scores and lower tramadol requirements, suggesting it was more effective in managing postoperative pain. This suggests group A could be a preferable approach for early pain reduction. Conclusion: Local port-site and intraperitoneal infiltration is a simple and effective method of post-operative pain control after LC and can be easily practiced after completion of surgery.